Solvent Effects on the Kinetic and Mechanism of N-Mannich Bases of 3-Hydrazonoindole-2-one - Saad Al-Garni, Tahani; M. Ismail, Amel; Al-Zaben, Maha; El-Faham, Ayman (Asian Journal of Chemistry, 2013)
N-Mannich base reaction of 3-hydrazonoindolin-2-one with piperidine in presence of formaldehyde was followed spectrophotometrically in a wide range of water-acetonitrile and water ethanol (10-70 v/v) and at different temperatures (40-60 ºC). The reaction obeys pseudo-first order kinetics. Addition of organic solvent to water decreases the rate of the reaction. A non-linear relation was observed for the plot of log kobs versus the reciprocal of the dielectric constant for the solvent used which suggested that there is a selective solvation by the higher polar solvent, i.e., by water molecules. The thermodynamic parameters DH*, DS* and DG* were calculated and discussed in terms of solvation effects. The determined isokinetic temperatures in both systems, revealed the existence of compensation effect arising from the strong solute-solvent interaction. Finally a suggested mechanism was proposed.